Natural Light‐Scattering Nanoparticles Enable Visible through Short‐Wave Infrared Color Modulation. Issue 8 (14th February 2018) - Kumar, Amrita; Osgood, Richard M.; Dinneen, Sean R.; Koker, Brian D.; Pang, Richard; Deravi, Leila F.
Abstract: Color is ubiquitous in nature; however, the ability to rapidly change color in response to environmental cues is unique to few biological systems. Cephalopods are one such system; they employ a sophisticated ensemble of optical organs that assist in adaptive coloration in different environments. While these animals have been a subject of research for decades, the photophysics underlying their color modulation is still not well understood. This is especially true in the context of their pigmentary chromatophore organs, which are considered one of the active elements of coloration. This paper describes diffuse and specular scattering originating in materials made from the nanoparticles that populate the chromatophore organs and shows for the first time how a film as few as two particle layers thick (≈1 µm) contributes to over 20% forward scattering in the visible, near‐infrared, and short‐wave infrared (SWIR) regions. The intensity of scattered light across this broad spectrum increases when films or fibers containing these nanoparticles are placed above a back‐reflecting material, suggesting a tunable feature that can be controlled under different conditions. This nano‐enhanced visible through SWIR scattering may lead to better spectral purity of reflected and back‐scattered light, illustrating an important role in color and future color‐changing materials. Abstract : An unlikely source for tunable visible through infrared light scattering emerges from nanoparticles isolated and processed from squid skin. Color and brightness in mimetic films and fibers built with these nanoparticles are controlled by varying the thickness of the particle layer and/or by combining a back‐reflector with a specific band pass, illustrating new materials applications for these biological nanostructures.